Eksistensi Amerika Serikat Sebagai Kekuatan Global - Hussein, Saddam (Global and Policy Journal of International Relations, 2013)
ABSTRACTCurrently, the global crisis has cause some major countries experiencing major crisesit also has no exception to the superpower United States today. United States as a superpower has experienced over-stretched that we can see in the two wars that occurred after the 911. This accident rise some countries confidence against the brave United States. And it is increasingly demonstrating the existence of the United States began replaced as a superpower or the ruler of the world. In 2010, the efforts of United States escape from two wars that they created himself has drained resources and undermining his authority as a superpower. And this year 2010 become a witness of how the United States busy to defend their position as a superpower.Keywords : United States, Superpower Country, Global PowerDOI:https://doi.org/10.33005/jgp.v1i01.2013